A case report of cough headache with transient elevation of intracranial pressure and bilateral internal jugular vein valve incompetence: A primary or secondary headache?. (March 2018) - Liu, Huanxian; Cao, Xiangyu; Zhang, Meichen; He, Mianwang; Li, Min; Song, Yangguang; Dong, Zhao; Yu, Shengyuan
Background: Primary cough headache (PCH) is precipitated by coughing or the Valsalva manoeuver (VM), and its underlying pathophysiology remains unclear. Case report: We report a case of recurrent cough headaches precipitated by VM with transient increase of intracranial pressure (ICP) diagnosed by measuring left sigmoid sinus pressure. Bilateral internal jugular vein valve incompetence (IJVVI) was also diagnosed by Doppler ultrasonography during a VM. Indomethacin was administered for over four months, and the headache had completely disappeared at the four-month follow-up. Conclusions: Cough headache might be associated with a transient increase of ICP induced by IJVVI, which might partially explain the pathophysiology of VM-induced headache. Detecting the internal jugular vein during a VM might be used as diagnostic procedure for patients who have PCH during resting and VM. If it is necessary, monitoring the ICP could be considered.